Changes in markers of body composition of professional male soccer players during pre-season - McEwan, G. P.; Drobnic, F.; Lizarraga, A.; Díaz, A. G.; Pons, E.; Iacon, A. D.; Unnithan, V. (Sports Medicine and Health Science, 2020)
To evaluate changes achieved in whole-body and regional (upper limbs, lower limbs, and trunk) estimates of body composition, twenty professional male soccer players (7 defenders, 7 midfielders, 6 forwards) underwent dual-energy x-ray absorptiometry (DXA) analysis at the beginning and end of pre-season. Measures included: mass, fat mass (FM), fat-free mass (FFM), and body fat per cent (BF%). Players` activity during on-field training sessions was monitored using Global Positioning System (GPS) units, with GPS data used to obtain estimations of energy expenditure (EE). Whole-body mass remained unchanged across the pre-season. Moderate significant increases and decreases were achieved in whole-body FFM (Pre: 59.58±5.27kg; Post: 60.61±5.18kg; p=0.001; d=0.87) and FM (Pre: 10.60±1.88kg; Post: 9.56±1.81kg; p=0.001; d=0.85), respectively. Moderate significant decreases were achieved in whole-body BF% (Pre: 14.4±2.3%; Post: 12.9±2.0%; p<0.001; d=0.94). No significant inter-positional differences were observed for the changes achieved in any global or regional estimate of body composition. Total EE was significantly correlated with ?FM (r=0.65, p=0.002), DeltaFFM (r=0.46, p=0.03), and DeltaBF% (r=0.67, p=0.002). The total EE of pre-season training accounted for 42%, 21%, and 45% of the variance in DeltaFM, DeltaFFM, and DeltaBF%, respectively. These findings suggest that the pre-season period is a suitable time for initiating favourable alterations in body composition following the off-season in elite soccer players.